ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) SIZE, BOPO TERHADAP PROFITABILITAS (Studi Perbandingan Pada Bank Domestik dan Bank Asing Periode Januari 2003-Desember 2007) - Purwana, Edward Gagah (JURNAL BISNIS STRATEGI, 2009)
The objective of this research is to analyze the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO), toward Profitability of Domestic Banks and Foreign Banks in January 2003 un December 2007. This research also used Chow Test to analyze the influence of Capita, Adequacy Ratio (CAR), LoaN to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO), toward Profitability between State Owned Banks and Foreign Banks.This research used time series data from Bank Indonesia's three monthly domestic Banks and Foreign Banks published financial reports. After passed the purposive sampling phase, the number of valid sample is 10 Domestic Banks and 10 Foreign Banks. This research used multiple regression analysis to analyze the data. This research also used Chow Test to analyze the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO), toward Profitability between Domestic Banks and Foreign Banks.Empirical evidence shows that Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) has a positive and significant influence toward profitability in State Owned Banks And on!y Size has positive and significant influenced toward profitability in foreign ben. The result of this research shows that adjusted R2 from Domestic Banks is 90,2% and Foreign Bankks is 45, 1 %. F lest shows that in simultant, Domestic Banks, Foreign Bank variable independent influence variable dependent. Chow Test result shows influence of Capital Adequacy Ratio (CAR), Loan to Deposite Ratio (LDR), Size, Operations Expenses to Operations Income (BOPO) toward Profitability between Domestics Banks and Foreign Banks. This research result can be consideration for investor in invested whether domestic bank and foreign bank must follow the flow of global competition changing to maintain survive, with this competition then needed for future research.Â